Complying with and enforcing of environmental law: a critical appraisal of the mechanisms used at the international and the European level. (1st January 2014) - Gizari-Xanthopoulou, Anna; Manou, Dimitra
Despite the vast number of environmental agreements and laws coming into force their impact are not the anticipated ones, as clearly seen from the degradation of the natural environment. This is largely due to ineffective enforcement of and compliance with the environmental obligations encompassed by all these laws and treaties. Thus, enforcement and compliance mechanisms are of paramount importance for the achievement of environmental conservation, as environmental results matter at the end of the day. This paper seeks to identify and assess the institutional mechanisms for enforcement of and compliance with international and European environmental law. It explores recent developments and provides a critical appraisal of the mechanisms and procedures developed globally and regionally with regard to the fulfilment of states' environmental commitments. It concludes with further steps which may enhance compliance and improve enforcement of environmental obligations at both the international and EU level.